1999
DOI: 10.1063/1.125429
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of island-like FePt crystallites with orientations

Abstract: Thin films of oriented island-like crystallites of L1 0 FePt separated by amorphous (a-)Al 2 O 3 were fabricated. The process took advantage of the overgrowth of ␣-Fe on Pt ''seed'' particles epitaxially grown on ͑100͒ NaCl and MgO substrates and the ordering reaction between Fe and Pt upon annealing at temperatures higher than 500 °C. The coercivities of the annealed ͑600 °C for 6 h͒ a-Al 2 O 3 /Fe͑1 nm͒/Pt ͑1.5 nm͒ films on both the NaCl ͑100͒ and MgO ͑100͒ substrates are higher than 3.3 kOe. Transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 9 publications
2
42
1
Order By: Relevance
“…The ordering temperature of 613 K for the L1 0 -FePtCu nanoparticles is about 260 K lower than that of the L1 0 -FePt nanoparticles fabricated by our electron-beam deposition. 7,18,19) By contrast, it is clearly shown that the intensity of 111 reflection is largely reduced as the substrate temperature increased, indicating the enhancement of h100i oriented growth under the higher substrate temperature.…”
Section: Evolution Of Atomic Orderingmentioning
confidence: 88%
See 1 more Smart Citation
“…The ordering temperature of 613 K for the L1 0 -FePtCu nanoparticles is about 260 K lower than that of the L1 0 -FePt nanoparticles fabricated by our electron-beam deposition. 7,18,19) By contrast, it is clearly shown that the intensity of 111 reflection is largely reduced as the substrate temperature increased, indicating the enhancement of h100i oriented growth under the higher substrate temperature.…”
Section: Evolution Of Atomic Orderingmentioning
confidence: 88%
“…Orientation control as well as isolation of nanoparticles has been achieved by epitaxial growth of FePt alloy onto heated MgO and/or NaCl substrates. 5,7) However, in order to obtain the L1 0 phase with high MAE, it is indispensable to perform the postdeposition annealing or substrate heating at high temperatures around 873 K. Furthermore a few article have taken the areal density of FePt nanoparticles into consideration. Based on such backgrounds, the current interests are concentrated on the fabrication of L1 0 FePt nanoparticles with orientation and high-areal density under the lower temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The requirement of noise reduction for extremely high magnetic recording density, e.g., from 100 Gb/in 2 to 1 Tb/in 2 , imposes the need for grain size being reduced below 10 nm with extremely uniform size distribution. 5 As a consequence, such small particles of the standard CoCrPtX type, will cause the thermal instability of magnetic recording because of superparamagnetic limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Most FePt nanoparticles were prepared with normal magnetron sputtering or electron-beam-evaporation techniques. [1][2][3][4] New techniques such as chemical synthesis and self-assembly methods have been developed recently to obtain FePt nanoparticles with very uniform particle size and narrow size distribution. 6 In this article FePt clusters are produced with a gasaggregation technique, in which magnetron sputtering is employed in the source.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been considerable interest in L1 0 ordered CoPt, Fe nanoparticles with the high magnetocrystalline anisotropy for extremely high density magnetic recording (EHDR) media [11][12][13][14][15]. The drive for the EHDR, i.e.…”
Section: Introductionmentioning
confidence: 99%